The Concept of Humanity from the Perspective of Maqāṣid al-Sharī‘ah - Moh. Husnul Affan; Asep Awaludin (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
It is widely mentioned that Sharia in Islam, especially the application of law (ḥudūd) is widely seen as treatment that is not in accordance with human rights. The conception of human rights and humanity still has various epistemological and theological problems. Human rights as discussed by the West are loaded with the paradigm of secular humanism which is very contradictory in Islam. This study discusses the suitability of the purpose of implementing maqāṣid al-sharī‘ah with humanity based on Islamic views. The implementation of Sharia has encountered many obstacles in the form of protests or rejections from many parties. In this article we argue that Muslims devise their own conception of human rights that is in accordance with the Islamic worldview. In the end, by the application of maqāṣid al-sharī’ah, Sharia can met ever-changing contemporary discourses.